2006
DOI: 10.1109/tbme.2006.879459
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Correlation Analysis Applied to Remove Muscle Artifacts From the Electroencephalogram

Abstract: The electroencephalogram (EEG) is often contaminated by muscle artifacts. In this paper, a new method for muscle artifact removal in EEG is presented, based on canonical correlation analysis (CCA) as a blind source separation (BSS) technique. This method is demonstrated on a synthetic data set. The method outperformed a low-pass filter with different cutoff frequencies and an independent component analysis (ICA)-based technique for muscle artifact removal. In addition, the method is applied on a real ictal EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
275
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(292 citation statements)
references
References 14 publications
1
275
0
4
Order By: Relevance
“…In Fig. 1, the artificial noise is added to a complete 12.5 hour EEG recording (using the publicly available data from [27], [28]). This long EEG record is then split into multiple shorter duration EEG sections, and the correlation in each section plotted against the duration of these shorter sections.…”
Section: Noise Correlationmentioning
confidence: 99%
“…In Fig. 1, the artificial noise is added to a complete 12.5 hour EEG recording (using the publicly available data from [27], [28]). This long EEG record is then split into multiple shorter duration EEG sections, and the correlation in each section plotted against the duration of these shorter sections.…”
Section: Noise Correlationmentioning
confidence: 99%
“…The amplitude of these artifacts commonly generated by ocular and muscle activities can be quite large and may thus mask the cortical signals of interest, bias the analysis and interpretation, and affect the performance of the BCI [14], [15]. Several blind source separation techniques have been proposed for signal preprocessing to remove such artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…In these novel EEG devices, dry electrodes act as substitutes for traditional wet electrodes; these dry electrodes can acquire real-time EEG signals for operational workplaces without requiring conductive gel/paste or scalp preparation in BCI applications. An online artifact removal technique based on canonical correlation analysis (CCA) [15] as a blind source separation used to remove artifacts is presented in Section III.A. The feasibility of rapid P3 detection using a radial basis function network (RBFN) [27] under a small number of EEG trials is demonstrated in Section III.B.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the method is applied to a real ictal EEG recording contaminated with muscle artifacts. The proposed method removed successfully the muscle artifact without altering the recorded underlying ictal activity [3,7].…”
Section: Introductionmentioning
confidence: 99%